2016
DOI: 10.1097/tp.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

Early Readmission After Kidney Transplantation

Abstract: Specific discharge level factors correlate with readmission irrespective of comorbidities and transplant complications. These findings may have important implications on discharge practice by aiding to identify which KTx recipients could be targeted for enhanced care transitions. Overall, potential opportunities for readmission reduction exist on multiple process levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…It also remains to be seen whether the combination of vintage and CIT has a synergistic association with long-term allograft survival; however, the further the time from the event, the harder it may be to draw causal inferences. We did not examine DGF because it is an endpoint that has multifactorial etiologies 29-32 and is likely to have stronger influential factors beyond CIT and vintage. CIT is a known independent risk factor for DGF, 29-31 and the consequences of DGF are difficult to overcome including increased complexity of management and readmission.…”
Section: Discussionmentioning
confidence: 99%
“…It also remains to be seen whether the combination of vintage and CIT has a synergistic association with long-term allograft survival; however, the further the time from the event, the harder it may be to draw causal inferences. We did not examine DGF because it is an endpoint that has multifactorial etiologies 29-32 and is likely to have stronger influential factors beyond CIT and vintage. CIT is a known independent risk factor for DGF, 29-31 and the consequences of DGF are difficult to overcome including increased complexity of management and readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified several risk factors for the 30-day readmission rate, such as recipient age, comorbid diabetes mellitus, length of stay, cytomegalovirus (CMV) serology negative, deceased kidney donation, delayed graft functioning and low glomerular filtration rate at discharge [ 9 , 14 , 15 ]. However, these studies focused on the short term [ [16] , [17] , [18] , [19] ], with a lack of long-term follow-up data.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from a cohort of 32,961 kidney transplant recipients treated by the Medicare system from 2000 to 2005 extracted from the US registry, EHR was 31%, ranging from 18 to 47% across transplant centers 32 - 35 . This large variation is mainly due to the characteristics of the recipient.…”
Section: Ehr Of Kidney Transplant Recipientsmentioning
confidence: 99%
“…The length of stay during the transplant hospitalization varied from 5 to 8 days among US centers. 32 - 35 , 38 . The main causes of EHR were related to infectious complications after surgery.…”
Section: Ehr Of Kidney Transplant Recipientsmentioning
confidence: 99%